THE DEVELOPMENT OF FLANKING FOLDS DURING SIMPLE SHEAR AND THEIR USE AS KINEMATIC INDICATORS - Grasemann B.; Stuwe K. (My University, 2001)
We used a numerical finite element simulation to model the formation of flanking folds around rotating planar structures (e.g. veins, faults or dykes) in a non-linear viscous medium during ideal simple shear. If the planar structure is much more viscous than its host it does not deform and flanking folds with no displacement along the structure develop. Their vergence is consistent with the overall sense of shear. However, if the planar structure is much less viscous than its host, strain is concentrated within the structure and a secondary shear zone is developed in which slip is opposite to the overall sense of shear. Then, flanking folds develop that have a vergence, which is incompatible with the drag on structure. If the deflection of markers is not clearly preserved, then such flanking folds can be easily misinterpreted as shear bands indicating a wrong shear sense. The deflection of the foliation in flanking folds is very similar to deformed asymmetric pull-aparts and can therefore help to interpret these otherwise ambiguous shear sense criteria. Because our model (ideal simple shear boundary conditions) fails to describe back-rotation of planar structures in rocks we speculate that shear band geometries are indicative for general shear.